Flowability of selected Malaysian herbal powders and their formulations - Etti, Christopher Joseph (2015)
This thesis presents a study on flowability of selected Malaysia herbal powders and their formulation. Orthosiphon stamineus, Eurycoma longifolia jack, Labisia pumila and Andographis paniculata powders and a freeze dried extracts of Labisia pumila which all have a wide industrial and human applications were used. This study evaluates flowability of the selected herbal powders based on conventional methods of flow measurements (like bulk and tapped densities, Carr index, Hausner ratio and angle of repose), with technological advanced, innovative methods of characterization of powder flow such as cohesion determination, shear cell for effective angle of internal friction and wall friction angle and the use of very recently automated powder flow analyzer (powder rheometer). Powders material properties like particle size, moisture content, tap, bulk and true densities were determined and their influence on flowability properties were evaluated. The effects of anti-caking agents (flow aids) on the powders using the powder flow analyzer were also described. The herbal powders were also formulated with sugar and creamer into herbal powder beverages mix and their flowability was also investigated. Labisia pumila powder was compressed into tablets using a stainless steel cylindrical uniaxial die of a 13-mm- diameter with compaction pressures ranging from 7 to 25 MPa. Two feed weights, 0.5 and 1.0g were used to form tablets and four compression models were used to describe and understand compressibility characteristics of the herbal powders. The strength of the tablets increased with increase in compaction pressure. Powders with smaller particle sizes gave more problems to flowability. Labisia pumila extracts with highest particle size range was freest with the least cohesion index,least angle of wall friction, least effective angle of internal friction as well as least angle of repose. The mean caking strength of powders reduced by the addition of 1% Silicon dioxide and potato starch respectively. The flowability properties of all the formulated mix was greatly improved based on enhancement of material properties. Toxicological studies of the formulated beverage mix on healthy female wistar rats showed the mix to be safe after the acute oral toxicity and sub-chronic studies was carried out for 28 days. In conclusion, this study enhances the understanding of powder flowability which can improve the development and formulation of herbal powder beverage mix